Asymmetric conjugate addition reactions - Bentley, S; Scott Bentley (2011)
This thesis is concerned with the asymmetric conjugate addition reactions of a range of chiral nucloeophiles. Chapter 1 introduces the conjugate addition reaction as a valuable carbon-carbon and carbon-heteroatom bond forming reaction in organic chemistry, and explores the asymmet- ric conjugate addition of a range of chiral and achiral carbon and nitrogen nucleophiles to a range of acceptors. Chapter 2 explores the use of the N-benzyl-N-(α-methylbenzyl)amino group as a chi- ral auxiliary, by employing the attempted conjugate additions of both N-benzyl-N-(α- methylbenzyl)hydrazine and N -benzyl-N -(α-methylbenzyl)hydroxylamine as chiral ammo- nia and water equivalents respectively. Chapter 3 describes the asymmetric and stereoselective preparation of a range of 4,4- disubstituted isoxazolidin-5-ones from the conjugate addition of lithium (S)-N-tert-butyl- dimethylsilyloxy-N -(α-methylbenzyl)amide. The isoxazolidin-5-ones are then globally de- protected via hydrogenolysis, giving rise to the corresponding β2,2,3-amino acids. Chapter 4 focuses on the development of a protocol to effect the conjugate addition of a chiral aniline equivalent. The scope of the reaction is delineated by varying both the nu- cleophile and the α,β-unsaturated ester. Finally, cyclisation of the β-N-arylamino esters to the corresponding tetrahydroquinolines is explored, and an application to the synthesis of the natural product (−)-angustureine is presented. Chapter 5 contains full experimental procedures and characterisation data for all com- pounds synthesised in Chapters 2, 3 and 4.